생육기간이 짧고 수당립수가 많은 자포니카 조생 사료용 벼 ‘조농’ - 박현수(Hyun-Su Park); 백만기(Man-Kee Baek); 김우재(Woo-Jae Kim); 김정주(Jeong-Ju Kim); 정종민(Jong-Min Jeong); 조영찬(Young-Chan Cho); 고종철(Jong-Cheol Ko); 정지웅(Ji-Ung Jeung); 정오영(O-Young Jeong); 이창민(Chang-Min Lee); 김석만(Suk-Man Kim); 김기영(Ki-Young Kim); et al. (Korean journal of breeding, 2021)
‘Jonong’ is an early maturing whole crop silage (WCS) japonica rice cultivar characterized by a short growth duration and numerousspikelets. It was developed to enhance the adaptability of WCS rice to double-cropping systems. ‘Jonong’ is derived from a cross between‘Binhae Col.#1’ and ‘Deuraechan’; ‘Binhae Col.#1’ is a semi-early maturing China rice germplasm with numerous spikelets on dense panicles,whereas ‘Deuraechan’ is a high-yielding japonica rice cultivar with numerous spikelets on long panicles. To diversify the genetic variationand shorten the breeding period, an anther culture method was applied to the F1 plants. ‘Jonong’ was selected through the pedigree method,yield trials, and local adaptability tests, with a high selection pressure for short growth duration and high biomass. The average heading dateof ‘Jonong’ was August 1st, which is 11 days earlier than that of ‘Nokyang’, the standard cultivar for WCS rice. Moreover, the growth durationof ‘Jonong’ is the shortest among all Korean WCS rice cultivars. The culm length of ‘Jonong’ is 88 cm, which 4 cm longer than that of‘Nokyang’ and the highest among all Korean early maturing rice cultivars. ‘Jonong’ has 149 spikelets per panicle, which is 30 more thanthat of ‘Nokyang’, and is the highest among all Korean early maturing rice cultivars. ‘Jonong’ exhibits stable premature heading and is tolerantto lodging. It is moderately resistant to leaf blast and resistant to the rice stripe virus. The feed value of ‘Jonong’ in terms of total digestiblenutrients is good and comparable to that of ‘Nokyang’. Furthermore, compared with ‘Nokyang’, ‘Jonong’ shows a similar level of dry matteryield and a higher rough rice yield. Therefore, ‘Jonong’, an early maturing WCS japonica rice with short growth duration and numerousspikelets, would be suitable for cultivating in winter forage crop-rice double cropping systems (Registration No. 7274). KCI Citation Count: 0